Front Cover: Carbonate‐Based Fluorescent Chemical Tool for Uncovering Carboxylesterase 1 (CES1) Activity Variations in Live Cells (ChemBioChem 12/2022). (20th April 2022) - Singh, Anchal; Gao, Mingze; Karns, Carolyn J.; Spidle, Taylor P.; Beck, Michael W.
Abstract : Carboxylesterase 1 (CES1) is responsible for the metabolism of many drugs, however, factors that modulate CES1 activity are poorly studied. In this research article, the self‐immolative properties of carbonates are exploited to generate a fluorescent chemical tool, FCP‐1, from a commercially available fluorophore. The ability of FCP‐1 to report on endogenous CES1 in live cells is demonstrated before this fluorescent chemical tool is deployed to develop an assay that can measure the activity differences between CES1 isoforms in live cells. More information can be found in the Research Article by M. W. Beck et al.